A randomized trial comparing the efficacy and safety of treating patients with type 2 diabetes and highly elevated HbA1c levels with basal‐bolus insulin or a glucagon‐like peptide‐1 receptor agonist plus basal insulin: The SIMPLE study. Issue 9 (28th June 2019) - Abreu, Marconi; Tumyan, Anna; Elhassan, Ahmed; Peicher, Katherine; Papacostea, Olivia; Dimachkie, Perihan; Siddiqui, Muhammad S.; Pop, Laurentiu M.; Gunasekaran, Uma; Meneghini, Luigi F.; Adams‐Huet, Beverley; Li, Xilong; et al.
Abstract: Aim: To compare the efficacy and safety of a glucagon‐like peptide‐1 receptor agonist (GLP1RA) plus basal insulin versus basal‐bolus insulin treatment in patients with very uncontrolled type 2 diabetes. Materials and methods: The SIMPLE study was a 6‐month pragmatic, randomized, open‐label trial testing the effectiveness of two approaches to treat patients with type 2 diabetes and HbA1c ≥10%. We randomized patients to detemir plus liraglutide or detemir plus aspart (before each meal). The primary endpoint was change in HbA1c; changes in body weight, insulin dose, hypoglycaemia and diabetes‐related quality‐of‐life were secondary outcomes. Results: We randomized 120 participants aged 47.4 ± 9.5 years, Hispanic 40%, African American 42%, diabetes duration 10 [25th‐75th percentile (6 to 15)] years, body mass index 37.2 ± 10.3 kg/m 2 . HbA1c decreased more with GLP1RA plus basal insulin [12.2% (95% CI 11.8% to 12.6%) to 8.1% (95% CI 7.4% to 8.7%)] compared with basal‐bolus insulin [11.8% (95% CI 11.5% to 12.2%) to 8.8% (95% CI 88.1% to 9.55%)]; estimated treatment difference (ETD) of −1.1% (95% CI −2.0% to −0.1%) (non‐inferiority margin 0.4% and P = .0001, superiority P = .026). Compared with basal‐bolus insulin, treatment with GLP1RA plus basal insulin led to a body weight ETD of −3.7 kg (95% CI −5.8 to −1.5; P = .001), fewer patients experiencing hypoglycaemia [66.1% vs 35.2% ( P = .002)], and greater improvements in general/current health perception, treatment satisfaction, and fear of hypoglycaemia, while taking a lower total daily dose of insulin [estimated treatment ratio 0.68 (95% CI 0.55 to 0.84)]. Conclusions: In patients with HbA1c ≥10% treatment with GLP1RA plus basal insulin, compared with basal‐bolus insulin, resulted in better glycaemic control and body weight, lower insulin dosage and hypoglycaemia, and improved quality of life. This treatment strategy is an effective and safe alternative to a basal‐bolus insulin regimen.